Hypothesis: Irisin is a metabolic trigger for the activation of the neurohormonal axis governing puberty onset. (October 2016) - Wahab, Fazal; Shahab, Muhammad; Behr, Rüdiger
Abstract: A large body of data suggests that body weight influences puberty onset and adult reproduction. However, the underlying mechanism of how body weight influences puberty onset and fertility is not completely understood. The hypothalamic neuronal circuit regulating reproduction is restrained by inhibitory signals during childhood. At the time of puberty, these inhibitory signals are weakened and supplanted by stimulatory signals that, in turn, stimulate the release of gonadotropin-releasing hormone (GnRH) – a hypothalamic neuropeptide governing reproduction. A number of studies, however, suggest that puberty commencement occurs when body (fat) weight reaches a certain threshold, which is critical for the initiation of puberty and for support of the adult reproductive function. Previously, various signals have been studied which might link body (fat) weight-related information to the hypothalamic neuronal network regulating reproduction. However, the nature of the signal(s) that may link body fat and/or muscle mass with the hypothalamic neuronal network governing reproduction is still unclear. It has been intuitively speculated that augmentation of such signal(s) will cause a restriction of inhibitory input and activation of stimulatory input to GnRH secreting neurons at the time of puberty onset. Therefore, the unveiling of such signal(s) will greatly help in understanding the mechanism of puberty onset. Recently, it has been shown that expression of fibronectin type III domain containing-5 ( FNDC5 ) mRNA in central and peripheral tissues upsurges during postnatal development, especially around the time of puberty onset. Moreover, the systemic level of irisin – one of the protein products of the FNDC5 gene that is secreted as myokine and adipokine – also rises during postnatal development and correlates with the timing of puberty onset. Therefore, we propose here that irisin might serve as a possible signal for linking body fat/muscle mass with the hypothalamic center governing reproductive function. We hypothesize that irisin acts as a trigger for the activation of the hypothalamic neuronal network monitoring the onset of puberty.